There is More to Stjórn than Biblical Translation - Kleivane, Elise (Novus Forlag, 2018)
Konungs skuggsjá stands out in Old Norse literature as an example of the speculum genre. Views differ when it comes to who the primary audience for Konungs skuggsjá was: Was it the king’s son(s) or the hirð, or was it directed towards a more general audience as a way of teaching a new royal ideology or how to move upwards in society? Even though we cannot know exactly what the person behind Konungs skuggsjá intended his work to do, we can be quite sure that the functions and the relevance of Konungs skuggsjá have changed through history and according to where it was copied and used. Its relevance for those copying it in Iceland in the fifteenth century was surely different than at the king’s court in last half of the thirteenth century. In the following, though, I will rather focus on aspects that were probably relevant when Konungs skuggsjá was composed, and the subsequent period, in order to shed new light on another Old Norse literary phenomenon: Stjórn. [.]